PERAN BADAN USAHA MILIK DESA (BUMDESA) BENING ARTA PRIMA DALAM PENINGKATAN EKONOMI MASYARAKAT DESA SUMBERBENING KABUPATEN TRENGGALEK - Dika Aji Prasetyo; Muhammad Alhada Fuadilah Habib (ITB AAS Indonesia Surakarta, 2023)
BUMDesa is an institution engaged in the management of village economic assets and resources that is capable of driving economic life in rural areas with most of the capital coming from natural resources and human resources owned by the village. This research aims to reveal what impacts the BUM Desa Bening Arta Prima provides as an increase in the economy of the people of Sumberbening Village. The method used is a qualitative method. The data used are primary data and secondary data. Data collection techniques carried out in this study were observation, interviews and documentation techniques. Interviews were conducted with village heads, managers of BUM Desa Bening Arta prima and the community. The results of this research found that the existence of BUMDesa Bening Arta Prima in Sumberbening Village was able to provide jobs, support the development of local community entrepreneurs, support community agricultural activities, and increase village income.